La crise psychiatrique à l’hôpital - Elodie Berenguer (Anthropologie & Santé)
Offering an ethnography of clinical judgements within hospital space, this article relies on an interactionist analysis of the institutional treatment of manic episodes. Defined as a state of agitation affecting people living with the diagnostic of bipolar disorder, manic episodes represent one of the major forms of psychiatric crisis. The present analysis focuses on interactions between professionals and hospitalized persons, and highlights four steps of treatment, which are correlated to both implicit logics and specific spaces: symptom generation and affective logic, symptom qualification and moral logic, symptom neutralization and disciplinary logic, symptom rationalization and compassionate logic. Governed by a moral economy of care, manic episode treatment can be seen as having a political role, which organizes hierarchized social relationships, including hospital topography as an actor of the microsocial construct of a negotiated order found in psychiatric institutions.